Compreensão oral e escolaridade em idosos: projeto envelhecimento e saúde - Luciana Peixoto Vianello (2014)
Introduction: Language is one of the important executive functions in the aging process, however, problems involving language comprehension in older adults requires efforts to identify influence of associated factors, especially in a population with socio-cultural disadvantage. The main challenge is directed to the limitations faced in the evaluation of communicative performance when it comes to seniors with great educational restriction. Objectives: 1) To describe the overall performance of elderly people in understanding spoken language through listening comprehension section of BDAE (Boston diagnostic Aphasia Examination). 2) To analyze the influence of education and reading frequency in variability of results obtained in BDAE. 3) To describe the performance of older adults in Word Discrimination subtest of the listening comprehension section of BDAE under the influence of age and education, comparing the results with the data proposed by Mansur et al (2005) for the cutoff for brazilian population. Methods: This study is an epidemiological population-based, cross-sectional design. 282 seniors were elected from a random sample of 405 individuals aged 60 or older living in a low-income community of Belo Horizonte, participants of Aging and Health project. The structured interview including demographic data, medical diagnoses self-reported, they were subjected, health-related behaviors and social support. The standardized questionnaire was applied: the quality of life questionnaire (SF-12), common mental disorder as measured by the GHQ-12, the BDAE to assess listening comprehension. Eligibility was determined by the Mini-Mental State Examination (18), the Snellen test (3), functional and listening preserved skills. Factors associated with worse performance in BDAE, defined as the lowest quartile of the distribution of the final scores were investigated using multivariate logistic regression. Moreover, the word discrimination subtest was evaluated with stratification of elderly age and education. The difference in the distribution of scores among the subgroups evaluated by Kruskal Wallis test. The cutoff point - reference Mansur et al. (2005) was used for comparison of results. Results: The final scores in the listening test BDAE were low. The result was the influence of education and age, there is an inverse correlation between them. Five variables were independently associated with worse performance in BDAE way: higher age, lower education, do not have reading often, now about own difficult in understand conversations and do not have good quality of life. In subtest word discrimination, do not have formal education was crucial to show the worst performance. More than 60% of the elderly were below the cutoff suggested by Mansur et al. (2005). Conclusion: The results of this thesis show great restraint in oral comprehension performance of older, mainly under the influence of low-schooling and no reading habits. This reality makes it difficult to elect a cutoff point for BDAE that discriminate subjects with a neurological illness in those with limited formal education.